Komunikasi Interpersonal Orang Tua dalam Meningkatkan Pendidikan Anak Pesisir di Dusun Kurandak, Kabupaten Deli Serdang - Imelda, Putri; Nurhanifah, Nurhanifah (UIR Press, 2025)
The purpose of this study is to find out how parents interpersonal communication patterns in continuing their children's education with the constraints of the educational environment in the Coastal Zone, as well as analyzing parental support strategies that can affect the process of continuing education. Interpersonal communication patterns and educational support strategies are considered to be strongly influenced by the closeness of parents to their children, with good interpersonal communication as the main mediating role. The research methodology is qualitative with a case study approach through in-depth interviews and supported by a literature review of previous studies on the subject. The results show that interpersonal communication does not work well due to differences in aggressive parental communication patterns and the form of parental support is not an indicator of success in improving education because children do not have benchmarks of achievement in academic and non-academic at school.